Repurposing agricultural support policies for improved nutritional outcomes and green and low-carbon development - Zhang, Yumei; Fan, Shenggen; Si, Wei; Lan, Xiangmin; Wang, Jingjing; Chen, Kevin Z. (2022)
China's economy has developed rapidly in recent years, achieved historic reductions in poverty, and has met the ambitious goal of creating a moderately prosperous society. In this new stage, the Chinese government has announced multiple development goals, including improving national nutrition and health, achieving green, low-carbon, and sustainable development, and achieving common prosperity, and made commitments to reach its carbon emission peak before 2030 and achieve carbon neutrality before 2060. Great changes have taken place in China's agrifood systems in this process, with a significant increase in agricultural productivity, extension of supply chains, an increased supply of agricultural products, and a significant improvement in residents’ food consumption, nutrition, and health. Agricultural support policies have played an important role in promoting agrifood systems transformation, increasing agricultural production, ensuring food quantity, and providing residents with abundant and diverse food.